The Influence of Work Environment On Work Productivity With Adaptive Behavior as an Intervening Variable - Febrina, Fadhilla (TAZKIA JURNAL, 2024)
The change in the work environment in the field of marketing and billing at PT Adira Multi Finance Madiun can be addressed by employees by behaving adaptively to changes in the work environment that occur. This study uses a quantitative approach with a path analysis model. The research population amounted to 76 people. Determination of the number of samples using the census method. The research instrument is a questionnaire with data analysis techniques using path analysis and Sobel test. The results of the study prove that: (1) The work environment has a positive and significant effect towards the work productivity of employees marketing and billing division at PT Adira Multi Finance Madiun; (2) The work environment has a positive and significant effect towards adaptive behavior in marketing and billing employees PT. Adira Multi Finance Madiun; (3) Adaptive behavior has a positive and significant effect towards work productivity in marketing and billing employees PT Adira Multi Finance Madiun; and (4) work environment affects work productivity in marketing and billing employees PT Adira Multi Finance Madiun through adaptive behavior as an intervening variable.